Benzothiadiazole-based organic dyes with pyridine anchors for dye-sensitized solar cells: effect of donor on optical properties. Issue 24 (17th June 2015) - Bolisetty, M.N.K. Prasad; Li, Chun-Ting; Thomas, K.R. Justin; Bodedla, Govardhana Babu; Ho, Kuo-Chuan
Abstract: New dyes containing pyridine anchoring group and different nitrogen-based heterocyclic electron-donating units linked via benzothiadiazole moiety have been synthesized and characterized by photophysical studies. Incorporation of benzothiadiazole extended the absorption onset into the lower energy region up to 600 nm. The dyes possessing vinyl linker between the heterocyclic donor and benzothiadiazole exhibited red-shifted absorption with high molar extinction coefficient than the dyes, which contain heterocyclic donor directly attached to the benzothiadiazole unit. The dyes exhibited acidochromism in the absorption spectra presumably due to the protonation of the pyridine nitrogen. These materials exhibited good thermal stability and their thermal-decomposition temperatures are in the range, 355–407 °C. The dye-sensitized solar cells fabricated using a dye containing phenothiazine donor showed power conversion efficiency of 1.97%. Electrochemical impedance studies reveal that the charge separation is highly dependent on the structural composition of the dyes. Graphical abstract: